UNIVERSAL ROTOR FOR ALL SYSTEMS USED TO SUBJECT FLUIDS TO CENTRIFUGAL ACCELERATIONS - Couillard, François; Legrand, Jack (2025)
A rotor for all systems used to circulate various single-phase or multiphase fluids, ranging from organic or non-organic solvents to CO2 in a liquid or supercritical phase in cells connected to each other by channels, the assembly being subjected to adjustable centrifugal acceleration and including precision temperature control for chemical or biochemical reactions and extractions, and purification and separation reactions and, for use in chemical and biochemical reactors. Such a rotor is formed of one or more discs stacked on top of each other, each being made up of circular sectors consisting of a circular half-sector and a circular half-sector, each being the mirror image of the other relative to the plane of the circular half-sector after they have been assembled opposite each other in a sealed manner. Their half-channels having respective links which form a link channel when the half-sectors are joined.